2022
DOI: 10.3390/ijerph19042144
|View full text |Cite
|
Sign up to set email alerts
|

Proposed Standard Test Protocols and Outcome Measures for Quantitative Comparison of Emissions from Electronic Nicotine Delivery Systems

Abstract: This study introduces and demonstrates a comprehensive, accurate, unbiased approach to robust quantitative comparison of electronic nicotine delivery systems (ENDS) appropriate for establishing substantial equivalence (or lack thereof) between inhaled nicotine products. The approach is demonstrated across a family of thirteen pen- and pod-style ENDS products. Methods employed consist of formulating a robust emissions surface regression model, quantifying the empirical accuracy of the model as applied to each p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Alternatively, other forms of smoking (e.g., IQOS, e-cigarettes, vaping, etc.) have been introduced as safe or less harmful than tobacco or shisha smoking, but these forms of smoking have not been extensively researched for their possible harmful health effects [42][43][44][45][46]. Nevertheless, some research results have confirmed that these types of alternative smoking types do have harmful health effects [43,[47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, other forms of smoking (e.g., IQOS, e-cigarettes, vaping, etc.) have been introduced as safe or less harmful than tobacco or shisha smoking, but these forms of smoking have not been extensively researched for their possible harmful health effects [42][43][44][45][46]. Nevertheless, some research results have confirmed that these types of alternative smoking types do have harmful health effects [43,[47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%